Instilling the influences of HRM practices and proactive personality on the career advancement of working women - Ali, Majid; Mohd Zin, Md. Lazim; Hassan, Zuraida (IJICC, 2020)
The career advancement of women has been a point of contentious consideration for decades. Despite the industrial policies, regulations, local government initiatives, and laws on gender discrimination, women still face challenges and issues particularly when considering their employment, education, career advancement, and the holding of public offices. Similarly, in terms of pay scale, women are offered less compared to their males in the same position. The current study examines the influences of HRM practices (recruitment and selection, training and development, compensation, performance appraisal, and succession planning) and proactive personality on the career advancement of working women. The current study considers a sample of 327 working women in supervisory, managerial, and director level position in manufacturing firms, and a total of 395 questionnaires were distributed. The findings showed that HRM practices (recruitment and selection, training and development, compensation, performance appraisal, and succession planning) positively and significantly influence the career advancement of working women. Furthermore, a proactive personality also influences a woman's career advancement positively and significantly; however, proactive personality as a moderating factor has a significantly negative effect. The findings of the current study were consistent with the literature; however, the current study introduced HRM practices and proactive personality into social cognitive career theory. The findings of the current study opens up new paradigms for future researchers to assess the factors that influence the career advancement of working women.